2009
DOI: 10.1017/s0142716409090134
|View full text |Cite
|
Sign up to set email alerts
|

A cross-linguistic and bilingual evaluation of the interdependence between lexical and grammatical domains

Abstract: The purpose of this study was to examine within and across language relationships between lexical and grammatical domains by focusing on measures of lexical diversity and grammatical complexity in Spanish and English. One hundred and ninety-six preschool and school-aged Latino children with different levels of English and Spanish proficiencies and different language abilities produced narratives in Spanish, English, or both. Analyses revealed strong associations between lexical (number of different words and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
81
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(97 citation statements)
references
References 63 publications
10
81
1
5
Order By: Relevance
“…The bilingual children with LI also produced semantically related errors but were more likely present non-responses. Along the same lines, a comparison of NDW in the narrative samples of kindergarten age bilinguals showed that children with LI used less diverse vocabularies in each of their languages relative to their typically developing peers (73.8 vs. 80.6 in English and 68.1 vs. 79.6 in Spanish) (Simón-Cereijido & Gutiérrez-Clellen, 2009). These findings indicate that NDW may be sensitive to language development and language ability in bilingual children as has been observed in other languages (e.g., English and Cantonese) (Hewitt, et al, 2005; Klee, et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The bilingual children with LI also produced semantically related errors but were more likely present non-responses. Along the same lines, a comparison of NDW in the narrative samples of kindergarten age bilinguals showed that children with LI used less diverse vocabularies in each of their languages relative to their typically developing peers (73.8 vs. 80.6 in English and 68.1 vs. 79.6 in Spanish) (Simón-Cereijido & Gutiérrez-Clellen, 2009). These findings indicate that NDW may be sensitive to language development and language ability in bilingual children as has been observed in other languages (e.g., English and Cantonese) (Hewitt, et al, 2005; Klee, et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Both Muñoz et al (2003) and Miller et al (2006) documented statistically significant growth in MLU over the early school years. MLU in both languages of bilingual children with LI is lower than that of their typically developing peers (5.5 vs. 6.23 in English and 5.2 vs. 5.8 in Spanish) (Simón-Cereijido & Gutiérrez-Clellen, 2009). These data, in combination with data showing that MLU increases in this time period for bilingual children, suggest that MLU may contribute to our ability to differentiate children with low language ability in both Spanish and English.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies investigating developing grammatical knowledge in bilingual children have compared progress in the two languages as a means of determining their degree of interdependence (Paradis & Genesee, 1996). Most of these studies have shown that grammatical development proceeds independently in each language and is largely tied to vocabulary acquisition in that language (Conboy & Thal, 2006; Marchman, Martínez-Sussmann, & Dale, 2004; Simon-Cereijido & Gutiérrez-Clellen, 2009), but some report interference across languages for specific structures (Austin, 2007). However, studies that have compared the development of grammatical knowledge in bilingual children to that of monolingual children acquiring one of the languages have typically shown delays in the bilingual group (Marinis & Chondrogianni, 2010; Müller & Hulk, 2001; Paradis, 2010).…”
mentioning
confidence: 99%
“…The goal has been to identify a measure of lexical diversity that is effective, yet minutely affected by language sample length. Studies have been conducted in various languages including English (Owen & Leonard, 2002;Heilmann, Nockerts & Miller, 2010;McCarthy & Jarvis, 2010;Kover et al, 2012;Fergadiotis, Wright & Green, 2015), Cantonese (Klee et al, 2004;Wong et al, 2010), Chinese-English bilinguals (Ooi & Wong, 2012) and Spanish-English bilinguals (Simon-Cereijido & Gutierrez-Clellen, 2009;Bedore et al, 2010). Unfortunately, not all of these studies used the same measure of lexical diversity indices or sample demographic.…”
Section: Introductionmentioning
confidence: 99%